The Potential of the Local Wisdom PjBL Model Applied to the Processing of Medicinal Plants in Talang Duku Village Jambi - Nirmala, Nirmala; Zurweni, Zurweni; Hamidah, Afreni (Integrated Science Education Journal, 2024)
Purpose of the study: This study investigates the integration of PjBL with local wisdom to develop an innovative PjBL-Ethnoscience learning model. Incorporating ethnoscience-based approaches into PjBL, this model aims to equip students with 21st-century skills. Specifically, the research explores the potential of this model in the context of medicinal plant processing in Talang Duku Village, Jambi. Methodology: A qualitative approach was employed, utilizing surveys, interviews, and participant observation to gather comprehensive data on current medicinal plant processing practices and the potential impacts of implementing the PjBL-Ethnoscience model. The study involved close interaction with local practitioners and students to understand this integrated learning model's practical applications and educational benefits. Main Findings: The findings reveal that the PjBL model's syntax effectively applies to medicinal plant processing activities. This integration enhances students' understanding of biological concepts related to plants and connects them with local cultural practices. The study demonstrates that such activities can serve as a robust foundation for biology education, particularly in plant-related topics, fostering a deeper appreciation of local knowledge and sustainable practices. Novelty/Originality of this study: This research presents a novel approach by merging the PjBL model with ethnoscience, particularly in medicinal plant processing in Talang Duku Village, Jambi. The study preserves cultural heritage and promotes sustainable practices by leveraging local wisdom. This innovative model provides a science learning base intimately connected to students' cultural backgrounds, making education more relevant and engaging. The PjBL-Ethnoscience model enhances academic learning and instills a sense of community and environmental stewardship among students.